Effect of graphene oxide with controlled stirring time - Mohd Akhair, Siti Hajar; Harun, Zawati; Jamalludin, Mohd Riduan; Shuhor, Muhammad Fikri; Kamarudin, Noor Hasliza; Yunos, Muhamad Zaini; Ahmad, Azlinnorazia; Azhar, Mohd Faiz Hafeez (AIDIC-Italian Association of Chemical Engineering, 2017)
In this study, the effect of graphene oxide (GO) with controlled stirring time was investigated. Five different samples with different stirring time of GO were used at 2 h, 4 h, 6 h, 8 h, and 10 h. The synthesization of GO was conducted using hummers’ method by adding graphite, hydroxide sulphuric, permanganate potassium, sodium nitrate, and hydroxide phosphorus. Hydroxide phosphorus was used as main peripheral material to increase the hydrophilic properties in GO performance. Characterization was carried out via XRD, FTIR and contact angle measurement. Results show that the appearance XRD peaks at range between 1,590 cm-1 until 1,750 cm-1 with increase stirring time. However, the lowest contact angle measurement of graphene oxide with high hydrophilicity effect was obviously shown by sample 3.